Modified Harrington’s procedure for periacetabular metastases in 89 cases: a reliable method for cancer patients with good functional outcome, especially with long expected survival - Kask, Gilber; Nieminen, Jyrki; Iterson, Vincent Van; Naboistsikov, Mihhail; Pakarinen, Toni-Karri; Laitinen, Minna K (Acta Orthopaedica, 2020)
Background and purpose — The pelvis is the 3rd most common site of skeletal metastases. In some cases, periacetabular lesions require palliative surgical management. We investigated functional outcome, complications, and implant and patient survival after a modified Harrington’s procedure. Patients and methods — This retrospective cohort study included 89 cases of surgically treated periacetabular metastases. All patients were treated with the modified Harrington’s procedure including a restoration ring. Lesions were classified according to Harrington. Functional outcome was assessed by Harris Hip Score (HHS) and Oxford Hip Score (OHS). Postoperative complications, and implant and patient survival are reported. Results — The overall postoperative functional outcome was good to fair (OHS 37 and HHS 76). Sex, age, survival > 6 and 12 months, and diagnosis of the primary tumor affected functional outcome. Overall implant survival was 96% (95% Cl 88–100) at 1 year, 2 years, and 5 years; only 1 acetabular implant required revision. Median patient survival was 8 months (0–125). 10/89 patients had postoperative complications: 6 major complications, leading to revision surgery, and 4 minor complications. Interpretation — Our modified Harrington’s procedure with a restoration ring to achieve stable fixation, constrained acetabular cup to prevent dislocation, and antegrade iliac screws to prevent cranial protrusion is a reliable reconstruction for periacetabular metastases and results in a good functional outcome in patients with prolonged survival. A standardized procedure and low complication rate encourage the use of this method for all Harrington class defects.